ACTIVITIES OF PUBLIC COUNCILS UNDER LOCAL PUBLIC ADMINISTRATION AUTHORITIES AT THE REGIONAL LEVEL - Kovbas, Ihor (VIEŠOJI POLITIKA IR ADMINISTRAVIMAS PUBLIC POLICY AND ADMINISTRATION, 2022)
This study covers topical issues of the modern state formation in Ukraine.The study was aimed at investigating the interrelations between individuals and subjects of public administration in the context of modernisation of Ukrainian society and the state. The purpose of this study was to identify the possibilities of introducing civilised aspects of relations between subjects of state power and civil society into management activities, which has been successfully implemented in management practice in countries bordering Ukraine: Poland, Romania, Hungary, the Baltic states, etc. The paper employed the following methods: analytical substantiation of the problems under study; focus group; expert survey; researchto-practice developments in the problems of relations between public councils and subjects of public administration, etc. Having studied the theoretical and practical components, the authors concluded that the public council as a temporary consultative and advisory body, formed under the executive authority to promote public participation in the development and implementation of national policy, is an integral component of a democratic society, which would help in bridging the gap formed over a ong time between the government and the population, the state and civil society, restore confidence in the authorities, form transparency and efficiency. The practical aspect of this problem can serve as a certain example for other countries, especially for the former republics of the USSR: Moldova, Belarus, Georgia, Armenia, Azerbaijan, etc.
Keywords: human dimension; democratic governance; subject of public administration; public organisation, empirical studies